Tuberculosis In Surabaya 1937-1942 - wati, Nur; Handayani, Sri Ana (Historia, 2021)
The writing of this article aims to discuss the problems (1) Why does tuberculosis appear in Surabaya? (2) What is the process of spreading tuberculosis in Surabaya? (3) What is the effort to eradicate tuberculosis in Surabaya ?. The method used in this study is the historical method which includes collecting sources, criticizing sources, interpreting, and writing history (historiography). The results of writing this article explain the emergence of tuberculosis in Surabaya caused by the poor ecology of the city. Poor ecology can be caused by human behavior in maintaining an environmental quality in Surabaya. Tuberculosis is a disease that spreads in Surabaya due to environmental factors such as irregular and dirty urban planning. In addition, social factors such as the daily behavior of people in Surabaya are also a cause of the spread of tuberculosis. Some efforts have been made by the government to eradicate tuberculosis, such as cleaning up slums and even fixing sanitation problems in the Surabaya area, and establishing a foundation called Stichting Centraal Vereniging tot Bestrijding der Tuberculose or commonly referred to as S.C.V.T. The foundation is aimed at patients with tuberculosis.